Two stages repair of proximal hypospadias: Review of 700 cases - Arvind Kumar Shukla; Aditya Pratap Singh; Pramila Sharma; Jyotsna Shukla (Wolters Kluwer Medknow Publications, 2017)
Objective: Surgical repair of hypospadias is challenging and problematic even for the most experienced specialists, and this is especially true when severe and complicated case is confronted. Many operations had been described for the management of this deformity. Materials and Methods: During the period from May 2004 to December 2015, we performed 700 cases with proximal hypospadias, at our institute in the Department of Pediatric Surgery by a single surgeon. Data were collected retrospectively and included patient's age at operation, degree of the hypospadias, degree of associated chordee, complications, and cosmetic outcome. All patients underwent 2 two-stage procedures with 9-12 months interval in between. Results: Seven hundred patients with proximal hypospadias were operated upon in a period of 11 years. Byars's 2 two-stage operation was used in all 700 cases. Neither complete disruption nor urethral diverticula occurred 2 two-stage procedures in the 700 patients. 677 (96.7%) patients had no complication. Fistula was present in 21 (3%) patients. There was no case of meatal stenosis in our study. Conclusion: Two stages procedure using the principles of Byar's technique is a versatile operation that can be used for 2 two-stage procedures the proximal hypospadias. It decreases the rate of fistula formation, disruption, and stenosis and gives a satisfactory cosmetic appearance.